Transcriptomics analysis provides insights into the heat adaptation strategies of an Antarctic bacterium, Cryobacterium sp. SO1 - Teoh, C. P.; Lavin, P.; Yusof, N. A.; González-Aravena, M.; Najimudin, N.; Cheah, Y. K.; Wong, C. M. V. L. (SpringerLink, 2023)
Most life forms on earth, including the cold-adapted bacteria from the polar regions, are being affected by global warming. To better understand how global warming may affect Antarctic bacteria, the heat-stress response of cold-adapted Cryobacterium sp. SO1 at the transcript level was determined in this study. A Cryobacterium sp. SO1 culture was grown at 20 °C which was its optimal growth temperature and subsequently exposed to a higher temperature of 25 °C that inhibited growth for 3 h. The transcriptome of strain SO1 was isolated, and RNA-sequencing (RNA-seq) was performed and analyzed using bioinformatics tools. The global transcriptome revealed 169 differentially expressed genes (DEGs), 108 of which were up-regulated and 61 of which were down-regulated. The strain SO1 DEGs were classified into seven categories: signal transduction, DNA modification and repair mechanisms, oxidative-stress defence, metabolism-related, cellular translational machinery, cell growth-related, and programmed cell death-related genes. Strain SO1 altered those genes to cope with the heat stress. Transposase gene up-regulation, in particular, probably promoted genome transposition in an attempt to generate genetically diverse cells in the population in the hope that some will be able to withstand the growth inhibitory temperature. Overall, the findings of this study shed some light on how Cryobacterium sp. SO1, and other Antarctic bacteria in general, will probably respond to global warming.